Histeryczny realizm, fantastyka, postmodernizm: Niewyczerpany żart (Infinite Jest) Davida Fostera Wallace’a - Stasiewicz, Piotr (Colloquia Litteraria, 2023)
The paper is an analysis of some peculiar aspects of David Foster Wallace’s most famous novel, Infinite Jest, concerning particularly the novel’s approach towards traditional realistic and fantastic literary strategies and a general literary worldbuilding. One particularly emphasized aspect of Infinite Jest is its connection with postmodernism regarded as a strategy of subversion of reader’s habits created by 20th century realistic and fantastic literary conventions. The novel’s unclear and problematic worldbuilding is explained as Wallace’s inclination towards literary irony and also as a typical postmodern strategy of parodying “honorable” literary forms and a general disregard of literature of “themes” and “meaning” in favor of emphasizing of act of reading in itself.